Learn Angular : related tools & skills. - Moere, Jurgen Van de; Rappl, Florian; Bodrov-Krukowski, Ilya; Smith, Jeff; Wanyoike, Michael; Motto, Todd (SitePoint Pty. Ltd., 2018)
Angular is not just a framework, but rather a platform that empowers developers to build applications for the web, mobile, and the desktop. This book provides an overview of some essential Angular tools--such as Angular CLI, Angular Augary, and Sublime Text--as well as outlining some must-have TypeScript tips. This book is for all front-end developers who want to become proficient with Angular and its related tools. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.